FACTORS ASSOCIATED WITH UTERINE TORSION IN CATTLE: A RETROSPECTIVE STUDY - ASHUTOSH TRIPATHI,; J. S. MEHTA, (The Bioscan, 2015)
In the present study the dystocia due to uterine torsion, cervical indilation, malplacement, emphysema and other causes turned out to be 33.03, 24.77, 14.22, 22.48 and 5.5 percent, respectively. Study on predisposing factors revealed that Rathi and non-descript cows are more prone to uterine torsion than H.F. while Jersey being least among the three with 75, 15.28 and 9.72 percent incidence, respectively. Susceptibility to torsion seemed to increase with age from 3 to 7 years while beyond 7 years it tends to decrease. Most of the animals referred with torsion were in 2nd and 3rd parity with 40.28 and 30.56% cases, respectively while primiparous and multiparous beyond 3rd parity seemed to be less prone. Most cases of uterine torsion reported were at full term while a few being preterm with 94.44 and 5.56% cases, respectively. Fetal gender seemed to play a significant role in predisposing animals to torsion as the proportion of male and female fetuses born to the animals with torsion were 63.89 and 36.11%, respectively. It seemed that slippery pakka floor make animals highly prone to torsion than kaccha floor and loose housing with 68.06, 20.83 and 11.11% cases, respectively.